Political institutions and FDI inflows in autocratic countries. Issue 7 (3rd October 2019) - Moon, Chungshik
ABSTRACT: Why do some autocratic countries attract more foreign direct investment (FDI) than others? Surprisingly, few studies have explored the considerable variation in FDI inflows to non-democratic countries. In this article, I argue that non-democratic countries with seemingly democratic political institutions, such as elected legislatures, attract more FDI inflow than others. This is because these institutions can (1) reduce the transaction costs of investment activities due to the relative transparency of the policy-making process, and (2) act as veto players, making the existing market-friendly policy changes difficult, and thus, promising a more stable investment environment. My empirical results support the main expectation that autocratic countries with legislatures attract more FDI than other autocratic countries, and the institutions' effects are conditionally modified by the quality of market protecting institutions.